ID 231 – Multicentric structural connectome analysis in 240 patients with amyotrophic lateral sclerosis. Issue 3 (March 2016) - Kassubek, J.; Turner, M.R.; Grosskreutz, J.; Abrahams, S.; Bede, P.; Agosta, F.; Govind, V.; Prudlo, J.; Ludolph, A.C.; Filippi, M.; Müller, H.-P.
Abstract : Objective: In-vivo assessment of ALS-associated white matter alteration patterns by diffusion tensor imaging (DTI)-based metrics have been included in the NiSALS neuroimaging concept (Turner et al., LancetNeurol 2011). The objective of this multicenter study was to assess structural connectivity in ALS at a large sample-size. Methods: Four-hundred-and-seven DTI data sets from patients with ALS ( N = 239) and controls ( N = 168) were collected from 8 international centers with different scanner systems and different DTI-protocols. Comparability of data with the aim of pooling was tested and differences were regressed out. Results: Beyond patterns of alterations in the corticospinal tracts, whole brain-based statistical analysis, after pooling of data sets from all centers, additionally captured significant white matter tract changes in the frontal lobe, brainstem and hippocampal regions, in keeping with the DTI-based correlates of post mortem neuropathological ALS-stages 1–4 (Kassubek et al., Brain 2014). Conclusion: This study using an unprecedented number of subjects has detected more wide spread changes than typical single-site studies.The observed pattern of fiber tract pathology has the potential to serve as a biomarker of disease and progression and as a read-out for future clinical trials. Key message: By this multi-centre approach, it was possible to non-invasively confirm the pathoanatomy of ALS in vivo .